2021
DOI: 10.5603/rpor.a2021.0028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative dosimetrical analysis of intensity-modulated arc therapy, CyberKnife therapy and image-guided interstitial HDR and LDR brachytherapy of low risk prostate cancer

Abstract: background:The objective of the study was to dosimetrically compare the intensity-modulated-arc-therapy (IMaT), cyber-Knife therapy (cK), single fraction interstitial high-dose-rate (hDr) and low-dose-rate (LDr) brachytherapy (BT) in low-risk prostate cancer.Materials and methods: Treatment plans of ten patients treated with cK were selected and additional plans using IMaT, hDr and LDr BT were created on the same cT images. The prescribed dose was 2.5/70 Gy in IMaT, 8/40 Gy in cK, 21 Gy in hDr and 145 Gy in LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The dosimetric analysis gives some explanations to the observed differences: D 0.1cm 3 and D 2cm 3 for anterior rectal wall was about 22%-28% higher with SBRT boost. These dosimetric differences in the dose to the anterior rectal wall were already mentioned in the literature [17][18][19]. In particular, in the study of Frohlich et al [19], D 2cm 3 to the rectum was 1.8 higher with SBRT compared to HDRB.…”
Section: B B a Amentioning
confidence: 70%
See 1 more Smart Citation
“…The dosimetric analysis gives some explanations to the observed differences: D 0.1cm 3 and D 2cm 3 for anterior rectal wall was about 22%-28% higher with SBRT boost. These dosimetric differences in the dose to the anterior rectal wall were already mentioned in the literature [17][18][19]. In particular, in the study of Frohlich et al [19], D 2cm 3 to the rectum was 1.8 higher with SBRT compared to HDRB.…”
Section: B B a Amentioning
confidence: 70%
“…These dosimetric differences in the dose to the anterior rectal wall were already mentioned in the literature [17][18][19]. In particular, in the study of Frohlich et al [19], D 2cm 3 to the rectum was 1.8 higher with SBRT compared to HDRB. Literature analysis clearly demonstrated that these differences transformed into important clinical consequences.…”
Section: B B a Amentioning
confidence: 70%
“…Fröhlich et al. [ 60 ] performed a comparison of two BT (LDR and HDR) and two EBRT (VMAT, CK) techniques using the CT images sets of 10 patients treated with CK. EQD2 doses were calculated and compared.…”
Section: Resultsmentioning
confidence: 99%
“…From these results, the authors conclude the superiority of HDR-BT for rectal and bladder dosimetry. Fröhlich et al [60] performed a comparison of two BT (LDR and HDR) and two EBRT (VMAT, CK) techniques using the CT images sets of 10 patients treated with CK. EQD2 doses were calculated and compared.…”
Section: Prostatementioning
confidence: 99%